Resilience to Stress: Lessons from Rodents about Nature versus Nurture. (June 2022) - Clinton, Sarah M.; Unroe, Keaton A.; Shupe, Elizabeth A.; McCoy, Chelsea R.; Glover, Matthew E.
Individual differences in human temperament influence how we respond to stress and can confer vulnerability (or resilience) to emotional disorders. For example, high levels of behavioral inhibition in children predict increased risk of mood and anxiety disorders in later life. The biological underpinnings of temperament are unknown, although improved understanding can offer insight into the pathogenesis of emotional disorders. Our laboratory has used a rat model of temperamental differences to study neurodevelopmental factors that lead to a highly inhibited, stress vulnerable phenotype. Selective breeding for high versus low behavioral response to novelty created two rat strains that exhibit dramatic behavior differences over multiple domains relevant to emotional disorders. Low novelty responder (bLR) rats exhibit high levels of behavioral inhibition, passive stress coping, anhedonia, decreased sociability and vulnerability to chronic stress compared to high novelty responders (bHRs). On the other hand, bHRs exhibit high levels of behavioral dis-inhibition, active coping, and aggression. This review article summarizes our work with the bHR/bLR model showing the developmental emergence of the bHR/bLR phenotypes, the role the environment plays in shaping it, and the involvement of epigenetic processes such as DNA methylation that mediate differences in emotionality and stress reactivity.